'A British Problem Affecting British People': Sickle Cell Anaemia, Medical Activism and Race in the National Health Service, 1975–1993. (17th July 2021) - Redhead, Grace
Abstract: Recent historiography has explored a contradiction at the heart of the British welfare state—it was founded on and supported by migrant and non-white labour, whose own healthcare and broader welfare state entitlements were neglected. This article explores how this contradiction was exposed and challenged by some of the health service's own workforce, who witnessed and contested racism in the National Health Service (NHS). This is discussed through the lens of the treatment of sickle cell anaemia (SCA), a genetic trait and disease more common in people of African, South Asian, Middle Eastern and Mediterranean descent, which has been highly racialized as affecting black people in particular. By pushing for improved responses to pain in sickle cell disease, and demonstrating the need for SCA screening in urban areas, healthcare professionals within the NHS—many of whom were black or migrant nurses, health visitors or doctors—articulated the status and entitlements of Black British citizenship.